Neurobiological mechanisms underlying the influence of parasitic infections on mental disorders: a literature review - Sosin, Aleksandra; Bednarz, Wojciech; Torbacka, Katarzyna; Rozkosz, Katarzyna; Kaczor, Joanna; Wróbel, Zuzanna; Jakubik, Olga; Wróbel, Natalia; Podlejska, Patrycja; Torbacka, Maja (Quality in Sport, 2025)
Parasitic infections pose a serious health threat worldwide, especially in developing countries, where they affect millions of people. Traditionally, they are seen mainly as something that impacts on the immune system and physiological functions but now more often potential mental health influence is also pointed out. In particular neurotropic parasites, like Toxoplasma gondii, Plasmodium falciparum, Taenia solium i Trypanosoma brucei are capable of modifying brain function which can lead to development of various mental disorders like schizophrenia, depression, epilepsy and sleep disorders. The purpose of this literature review is to analyze the available research on neurobiological mechanisms that show how parasites influence brain function and behaviour. Attention was given to main mechanisms such as changes in neurotransmission, microglial activation, inflammatory responses and structural changes in the brain. In the research results of brain imaging studies (MRI PET) were discussed. They can help understand these mechanisms in detail. Based on literature review, the role of environmental factors and comorbid conditions are also presented. Conclusions indicate the necessity of further research, that will allow understanding of the neurobiological mechanisms of parasitic infections and their influence on mental health.